2006
DOI: 10.1002/chem.200600207
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer in Nonpolar Solvents in Fullerodendrimers with Peripheral Ferrocene Units

Abstract: Two new fullerodendrimers, with two and four ferrocene units on their periphery, have been synthesized by 1,3-dipolar cycloaddition reactions between the corresponding azomethine ylides and C(60). These new compounds have been studied by using cyclic voltammetry and UV/Vis spectroscopy. Weak intramolecular interactions between the fullerene cage and the ferrocene groups have been found. The photochemical events of both fullerene-ferrocene dendrimers have been probed by means of steady-state and time-resolved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…First, the dual-donor systems are better than the monodonor systems in obtaining prolonged charge-separation states with the trends as reported for the multidonor systems. [9,10] The second point revealed in the present study is the effect of the bridges (pyrazoline and isoxazoline rings) used to connect the donors to the fullerene moieties; the pyrazoline ring acts as a better bridge than isoxazoline in the sense of high charge-separation efficiencies and slow charge-recombination rates.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…First, the dual-donor systems are better than the monodonor systems in obtaining prolonged charge-separation states with the trends as reported for the multidonor systems. [9,10] The second point revealed in the present study is the effect of the bridges (pyrazoline and isoxazoline rings) used to connect the donors to the fullerene moieties; the pyrazoline ring acts as a better bridge than isoxazoline in the sense of high charge-separation efficiencies and slow charge-recombination rates.…”
Section: Discussionmentioning
confidence: 98%
“…Hydrazones 4a-c were prepared in good yields (65-90 %) by the reaction of aldehydes 3a-c [10,18] with 4-nitrophenylhydrazine in refluxing EtOH. [19] Two different procedures were used for the preparation of pyrazolo-fullerenes 1a-c. Derivatives 1a and 1b were obtained (in 19 and 15 % yields, respectively) by the reaction of 4a and 4b with N-chlorosuccinimide (NCS) in CHCl 3 at 0°C and subsequent addition Scheme 2. of C 60 and Et 3 N in toluene at room temperature to afford cycloadducts 1a and 1b.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Xu et al studied the influence of solvent viscosity on the aggregation of LMOGs [16]; Perez et al investigated the solvent effect on the electron transfer of ferrocene derivatives [17]. Although a tremendous amount of experimental work has been devoted to the investigation of conductive-gel systems, theoretical support is still needed to address critical problems such as the interaction of solvent and gelators during aggregation, the phase transition of gels, and the electron transport properties in gel systems.…”
Section: Introductionmentioning
confidence: 98%
“…[9] The nanosecond transient absorption spectral studies revealed efficient photoinduced charge separation even in toluene as solvent, which is prospective for wide applications in non-polar media such as polymer films. Interestingly, when the same donor moiety Scheme 1.…”
Section: Introductionmentioning
confidence: 99%